An iterative approach for obtaining nonlinear frequency of a conservative oscillator with strong nonlinearities - Mohammadian, M.; Pourmehran, O.; Ju, P. (Прикладная механика, 2018)
An iterative procedure is suggested for obtaining the higher-order approximate solutions of a conservative system comprising an oscillator with cubic and quintic restoring force function. The proposed method is similar to the traditional harmonic balance methods but unlike them the obtained from the previous step errors are considered in the present step to increase the accuracy of the solution. A comparison of results with those obtained by exact solution and other approximate analytical techniques confirms an accuracy of the method. It is shown that the achieved approximate solutions are valid for both small and large amplitudes of oscillation and can meet the exact solutions with a high level of accuracy in the lower-order of approximations. Furthermore, using the obtained analytical solutions, the effect of cubic and quintic terms on the frequency is discussed. Запропонована ітераційна процедура для отримання наближених розв’язків високого порядку консервативної системи, яка містить осцилятор з відновлювальною силою, що описується третім і п’ятим порядками нелінійності. Запропонований метод аналогічний до класичних методів гармонічного балансу, однак на відміну від них тут похибки, отримані на попередньому кроці, розглядаються на наступному кроці з метою підвищення точності розв’язку. Порівняння результатів з результатами, отриманими як точний розв’язок і іншими наближеними аналітичними методиками підтверджує точність методу. Показано, що отримані наближені розв’язки вірні як для малих, так і для великих амплітуд коливань і можуть узгоджуватись з точним розв’язком з високим рівнем точності при низьких порядках наближень. Далі обговорюється вплив членів третього і п’ятого порядків на основі отриманих аналітичних розв’язків.